How people regard the mine establishment in Kaunisvaara, Tapuli and Hannukainen areas - Waara, Peter; Berglund, Leif; Soudunsaari, Leena; Koskimäki, Ville (Luleå tekniska universitet, Arbetsvetenskap, 2008)
Godkänd; 2008; Bibliografisk uppgift: A baseline study of socio-economic effects of Northland Resources ore establishment in northern Sweden and Finland; 20090203 (biem)